Expression of growth-related genes in muscle during fasting and refeeding of juvenile Atlantic halibut, Hippoglossus hippoglossus L. - Johnston, Ian Alistair; Fernandes, J M O; Solberg, C; Johnston, I A (Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, 2009)
The aim of this study was to establish a fasting-refeeding protocol to investigate the expression of growth-related genes during the transition between catabolic and anabolic states in Atlantic halibut (Hippoglossus hippoglossus L). Juveniles of similar to 950 g were maintained at ambient temperature (5-8 degrees C) until the 1st of May, then fasted for two months and refed for two months at 7.7-8.0 degrees C under continuous low light. Fast epaxial myotomal muscle was sampled at -64 d (days), -38 d, 0 d (start of refeeding), 3 d, 7 d, 14 d, 30 d and 60 d. Average body mass was unchanged over the fasting period but increased by 24.4% following 60 d refeeding. qPCR was used to analyse the stability of expression of five potential reference genes (Eef2, Fau, 18S rRNA, Actb and Tubb2) with GeNorm and Normfinder. Expression of the growth-related genes, cathepsin B (ctsb), cathepsin D (ctsd), insulin-like growth factor-I and II (IGF-I and II) and insulin-like growth factor-I receptor I a (IGF-IRa) was normalised using the geometric average of the two most stable housekeeping genes, Fau and 18S rRNA. IGF-I mRNA showed a transient 2.6-fold increase in abundance with refeeding at 7 d whilst transcripts for IGF-II and lGF-IRa were elevated during fasting and decreased 3.8-fold and 3-fold between the 0 d and 3 d samples respectively. Ctsb expression increased between -64 d and 0 d and then decreased similar to 10-fold by 14 d refeeding. In contrast, ctsd was relatively unaffected by the fasting-refeeding cycle, showing a modest (similar to 35%) transient decrease in expression between the 0 d and 30 d refeeding samples. It was concluded that the experimental protocol adopted and housekeeping genes identified were suitable for investigating the catabolic-anabolic transition in halibut skeletal muscle. (c) 2008 Elsevier Inc. All rights reserved.